Heat transfer and friction loss analysis of a novel eco-friendly colloidal suspension in flow passages / Kaviraj Jayaraman - Kaviraj , Jayaraman (2019)
Invention of heat exchanger can be considered as once of the most important inventions of time. Heat exchangers are important equipments with various industrial applications such as power plants, HVAC industry and chemical industries. The are various fluids that are used as working fluid in the heat exchangers. These fluids are water, oil, and ethylene glycol are some of the commonly used working fluids. A minor improvement in the working principle of heat exchanger may yield a much bigger outcome at a lesser cost. This idea has always interested researchers. Hence, researchers have conducted various studies and investigations to improve the heat exchanger be it from material or heat transfer point of view. In terms of heat transfer, they noticed that the conventional working fluids have a relatively low thermal conductivity and properties. There has been attempts to create solid particles suspended mixture. This invention faced some setback whereby the pressure drop was compromised, sedimentation occurred or even erosion, resulting in higher cost of maintenance. A group researcher discovered a new class of colloidal suspension fluid that met all the demands and characteristics of a heat exchanger. This novel colloidal suspension mixture was then and now addressed as “nanofluid”. In this study, phenolic acid functionalized graphene nanoplatelets nanofluids will be synthesized. The thermo-physical properties, thermal conductivity, density, viscosity, specific heat capacity and heat transfer coefficient will be studied upon. The flow of the nanofluid will be of turbulent fully developed type in a circular and square tube. All the nanofluids were prepared without adding surfactant but was put through sonication process. No sedimentation was observed. The experimental data for all the prepared nanofluids have shown significant enhancement in thermal conductivity and heat transfer coefficient in comparison to the corresponding IV base fluid the water data. In this investigation, some improved empirical correlations were proposed based on the experimental data for evaluation of the Nusselt number and friction factor. Keywords: Heat exchanger; Nanofluids, Heat transfer coefficient, Nusselt number; Pressure drop; Thermo-physical